Management Improving the Quality of Graduates of the Management Study Program at Islamic Higher Education - Moch. Ali Imrom; Iim Wasliman; Nandang Koswara; Adjat Sudrajat (International Journal of Science Education and Technology Management, 2023)
Management problems of Quality Improvement Graduates of Management Study Programs at Islamic Higher Education are unsolved problems in line with the complexity of environmental changes, both in terms of planning,organizing,implementation and evaluation.Departing from this thought, it becomes something very interesting to study more deeply about quality management in higher education and its determination factors, to produce accurate, valid, and objective data, so that it is expected to be able to answer problems with a value-free scientific spirit, especially The Management Study Program located at the Kusuma Negara College of Economics Jakarta and the As-Syafi'iyah Islamic University (AIU) in the Jakarta City area. This study aims to reveal and analyze the quality improvement management of management study program graduates at Islamic universities in Jakarta.The research approach used is qualitative with the data collection method used, namely the case study method through direct observation where the researcher sees firsthand the symptoms or events that occur and analyzes the events found in the field that are adapted to the research problem. Data collection techniques used are observation (observation), interviews, documentation studies. Regarding data analysis techniques using non-statistical analysis techniques. In general, there are similarities in the management process for improving the quality of university graduates to improve the quality of graduates at the Islamic University of As Syafi'iyah and STIE-KN, namely to improve the reputation of the institution and as an entry point to achieve graduate quality in a sustainable manner. Besides the similarities, there are also differences in the basic values ​​that underlie the implementation of quality assurance between AIU and STIE-KN, related to their different institutional visions and goals. The Management of the Internal Quality Assurance System at AIU and STIE-KN makes a positive contribution to improving the quality of graduates. This is reflected in the implementation of the Teaching, Research and Community Service Program, standardized through the policy of establishing a Graduate Quality Improvement Unit at AIU and a Graduate Quality Improvement Institute at STIE-KN. However, it is still limited to focusing on the academic field (only focusing on the learning aspect). This research is expected to provide input as a source of information about the quality of the internal quality assurance system process of private universities as a basis for mapping to determine quality improvement policies in higher education units, especially universities. The Ministry of Education and Culture continues to disseminate information on improving the quality of graduates by providing assistance and support in the process of preparing and setting quality standards and their development in order to broaden understanding of the education quality assurance system, so that all universities are able to manage improving the quality of graduates properly and have an impact on the quality of graduates according to the National Education Standards (NES).